Preliminary design and exploration of vibration-mediated smart adhesives utilizing viscous and viscoelastic materials - Sim, Brian Chuan Jie (Nanyang Technological University, 2024)
Geckos are masters of adhesion. Gecko adhesives can attach to a surface with a strong adhesion via van der Waals dispersion forces between their foot hairs (or setae) and the adherend, and then manage to detach from the surface rapidly (~15 ms) through peeling. This has inspired many gecko-inspired fibrillar adhesives, which have great potentials in various areas like soft robotics for outer-space or deep-sea exploration, objects picking in industrial line and our daily life. Currently, the adhesion strength of gecko-inspired fibrillar adhesives is limited to the order of around 117 kPa to ensure a relative fast response speed of around 200 ms. Another adhesion technique inspired by snails exploits the properties of Shape Memory Polymers (SMPs), which achieves ultra-high adhesive strength on the order of MPa through the shape-locking effect during the rubber-to-glass (R2G) transition, and large adhesion switchability (more than 1000) relying on the shape memory effect during the glass-to-rubber (G2R) transition. However, most existing SMPs, which are thermally controlled, suffer from slow response speed (more than 30 s) when attaching and detaching from surfaces. Currently, the trend of such smart adhesives such as gecko-inspired fibrillar adhesives and SMP adhesives shows that generally the stronger the adhesion strength, the longer the response time, which has limited the application of the smart adhesives in conditions requiring both high-payloads and rapid response speed. However, there is potential to break this trend and develop a smart adhesive with both very high adhesion strength and rapid response speed according to the Time-Temperature Superposition Principle (TTSP), which tells that the short-term behaviour of viscous and viscoelastic materials at higher temperatures is similar to the long-term behaviour at some lower reference temperature. Hence, this project aims to conduct preliminary research to utilize mechanical vibrations, which can be switched on/off and transmitted quickly in materials, to realize rapid switching of R2G transition of viscous and viscoelastic materials via the TTSP. After a systematic review and comparison, a viscoelastic material - Silly Putty – was chosen and encased within a flexible Ecoflex silicone casing to develop a potential smart adhesive. Two setups, with the modal exciter and the piezoelectric transducer to generate the actuation vibrations, were constructed and utilized to explore the influence of vibrations on the recovery of a glass sphere embedded into the adhesive. From vibrations generated from the modal exciter with an actuation frequency of 30 kHz and voltage of amplitude 10 peak-to-peak voltage (Vpp), the glass sphere embedded in the adhesives recovered 53 mm after 100 s, smaller than the 60 3 mm when the vibrations were switched “off” and demonstrated noticeable delayed recovering of 7 mm compared to the control experiment. Similarly, in the experimental using the set up with the piezoelectric transducer, the smart adhesive under the actuation vibrations of the piezoelectric transducer demonstrated delayed recovering of 2 mm compared its control experiment. In general, when induced by high-frequency vibrations generated from both the modal exciter and a piezoelectric transducer, the smart adhesive was able to demonstrate noticeable induced R2G shape-locking effects after being indented by a glass sphere. These preliminary results demonstrated the applicability of using vibrations to delay the recovery of the deformation during the contact, thus indicating the potential of using vibrations to realize rapid R2G transition for full shape locking instead of temperature. In conclusion, the proposed method in this preliminary research project to generate high-frequency vibrations to induce R2G transition in viscous and viscoelastic materials via the TTSP has been successfully validated. By implementing a radio frequency power amplifier along with other alternative smart materials utilising the experimental set ups discussed in this project, smart adhesives with even greater adhesion strength and rapid response speed could potentially be developed in the future. Such novel smart adhesives would make great impacts in many robotics and technological applications.